Unraveling reforms? Cotton in the 2018 Farm Bill - Glauber, Joseph W. (American Enterprise Institute, 2018)
Among the reforms enacted in the 2014 Farm Bill, few were more significant than the changes made to the suite of federal subsidy programs for cotton. Direct and countercyclical payments were eliminated and replaced by a heavily subsidized supplemental insurance program, the Stacked Income Protection Plan (STAX), a program designed and promoted by the US cotton industry. Those changes were put in place to resolve a long-standing trade dispute brought by Brazil to the World Trade Organization (WTO) against US cotton price and income support programs. The settlement successfully concluded the dispute and forestalled imposition of substantial damages against US goods and intellectual property that had been awarded to Brazil through WTO arbitration. Today, the US cotton industry is no longer enamored with the program they once championed. Participation in STAX by US cotton producers has been far lower than anticipated, and the US cotton industry has put forward proposals to make cotton producers again eligible for countercyclical price protection. The proposals have been touted as budget neutral, but given the volatility of cotton prices, budget exposure to large outlays is likely. Moreover, providing support to maintain high production levels in the face of lower market prices leads to market distortions, which only prolong market downturns. Those policies can have detrimental effects on world prices, which penalizes foreign producers, many of those in poor developing regions such as Sub-Saharan Africa. New price-based programs for cotton will also likely reignite trade tensions with Brazil, which could result in another trade dispute with potentially large consequences for US agriculture.